BCT554: Manufacturing technology / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2022)
The general aims of the course is to provide sufficient knowledge and understanding of the manufacturing technology in terms of production planning and control, machining process and manufacturing tools and also quality control. The course will include exposure to deal with relevant parties involved in manufacturing of IBS components. The students will be exposed to the principle of Industrialised Building System (IBS) followed by the method of manufacturing technology and IBS standards.